The Alexandrian Edition of Alcaeus - Ford, Thomas, (Schöningh and Fink History Early Modern and Modern History E-Books Online, Collection 2026., 2025)
This study provides the most extensive survey hitherto of what is known about the edition of the poetical works of Alcaeus, the soldier, partisan and singer from Lesbos who lived around 600 BC. It considers the evidence of Alcaeus' manuscripts and of references to his work in other sources to try to reconstruct, insofar as possible, the edition of his poems created by the scholars of Alexandria in the 2nd century BC. In doing so, it makes a range of new observations regarding how poetry was edited more generally and how Alcaeus' life was incorporated into his books.